2017
DOI: 10.5137/1019-5149.jtn.21095-17.0
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial epidermoid lesions: our experience of 38 cases

Abstract: Epidermoid lesions can develop anywhere in the cranial cavity. Like other space occupying lesions they often present with symptoms of raised ICP and with specific neurological deficits depending on location of the tumour. Surgical outcome is excellent with low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 9 publications
1
20
1
Order By: Relevance
“…Intracranial ECs are slowly growing, congenital anomalies occurring most commonly in the CPA. Due to the gradual mass effect, 3 ECs symptomatize in a wide range of age (between 20 and 60 years) with peak occurrence at around 40 years of age. [5][6][7] In our study, there was a slight female predominance compared with other studies which reported similar incidence in both genders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intracranial ECs are slowly growing, congenital anomalies occurring most commonly in the CPA. Due to the gradual mass effect, 3 ECs symptomatize in a wide range of age (between 20 and 60 years) with peak occurrence at around 40 years of age. [5][6][7] In our study, there was a slight female predominance compared with other studies which reported similar incidence in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…2 It may occur in other locations such as the suprasellar and the temporal regions. 3 ECs are slowly growing and may present with symptoms of elevated intracranial pressure (ICP) or symptoms of cerebellar, brainstem, and/or cranial nerves dysfunction. 4 MRI is the investigation of choice with diffusionweighted imaging sequence that distinguishes EC from arachnoid cyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Although these lesions are slow growing and pliable, they can adhere to or encase adjacent vessels and nerves. 4 Therefore, although a complete resection may offer long-term cure and a normal life expectancy, 22 it can carry a high risk of morbidity. Piece meal reduction in the mass, with gentle teasing of the capsule, is the ideal technique for resection of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is the imaging modality of choice for these lesions, with diffusion-weighted imaging (DWI), which helps differentiate these from their most common differential diagnosis, that is, arachnoid cysts. 4 The treatment of choice for these lesions is radical surgical resection. Although these tumors cross cisternal boundaries, majority of them can be resected with low morbidity, mortality, and recurrence with meticulous microsurgical techniques avoiding dreaded compilations of aseptic meningitis, neural deficits because of manipulation, and vascular injury.…”
Section: Introductionmentioning
confidence: 99%